Antibacterial activity of active fraction of sweet corn hair extract (zea mays f saccharata kornicke & werner) against methicillin resistant staphylococcus aureus (MRSA) growth - Juliani Khurfatul Jannah; Yuvianti Dwi Franyoto; Wulandari Wulandari; Jena Hayu Widyasti (Journal of Health Management and Pharmacy Exploration, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a Staphylococcus aureus bacterium that is resistant to methicillin-type antibiotics. This study aims to determine the antibacterial activity of the active fraction of sweet corn hair extract on the growth of Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria. Extraction was carried out by the remuneration method in 70% ethanol. In fractionation, liquid vacuum column chromatography with n-hexane, ethyl acetate, and methanol solvents was used. The fraction with the largest clear zone of methanol (100%) is with a clear zone diameter of 0.752 cm. Testing the antibacterial activity of ethanol extract at concentrations of 10%, 15%, and 20% obtained by clear zone with an average of 1,013; 1,073; 1,159 cm and in the active fraction with an average of 0,703; 0.903; 1,004 cm. Ciprofloxacin 0.005% was used as a positive control and DMSO as a negative control. The results showed that ethanol extract and an active fraction of sweet corn hair (Zea mays f saccharata Kornicke & Werner) had antibacterial activity against Methicillin-Resistant Staphylococcus aureus (MRSA). One-way ANAVA test results showed that there were significant differences in providing antibacterial activity (p> 0.05) between ethanol extract and active fractions at concentrations of 10%, 15%, and 20%. Flavonoid compounds, alkaloids, saponins, tannins, and triterpenoids in the active fraction of corn hair have antibacterial activity against MRSA bacteria.